Empowering Indonesian Science Learners through Independence, Environment, and Achievement: Memberdayakan Pembelajar Sains Indonesia melalui Kemandirian, Lingkungan, dan Prestasi - Rifqiyah, Ulfatur; Efendi, Nur (Indonesian Journal of Education Methods Development, 2024)
This study investigates the impact of student learning independence and perceptions of the learning environment on science learning outcomes at SMPN 1 Gempol. Utilizing non-experimental quantitative research with a correlational Ex post facto design, data from 293 students were analyzed using stratified random sampling. Results reveal significant positive correlations between student learning independence, perceptions of the learning environment, and science learning outcomes. These findings emphasize the importance of fostering student independence and creating conducive learning environments for enhancing science education outcomes at SMPN 1 Gempol. Highlight: Quantitative Analysis: Statistical clarity in assessing learning independence and environmental perceptions. Learning Independence: Crucial for science learning outcomes and student success. Perception and Environment: Impact on academic achievement in science education. Keyword: Science education, student learning independence, learning environment, SMPN 1 Gempol, quantitative research